2008
DOI: 10.1007/s11270-008-9693-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Heavy Metal Phytoextraction from Marine Dredged Sediments Comparing Conventional Chelating Agents (Citric Acid and EDTA) with Humic Substances

Abstract: Laboratory experiments were carried out to examine the effects of chelating agents on heavy metal extraction from slightly contaminated dredged sediments from the port of Livorno (Italy). Ethylene diamine tetraacetate (EDTA), citric acid (CA) and humic substances (HS) were tested in two different concentrations each: 120 and 480, 500 and 2,000, 500 and 1,000 mg/l, respectively. Solubilisation of heavy metals (Cu and Zn) was observed for both EDTA and HS in the extraction kinetic experiments: 58% of the total C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 31 publications
4
26
0
Order By: Relevance
“…The effect of compost on Cd bioavailability could be related to chelating/complexing reactions by acid functional groups of humic substances that can reduce the precipitation as hydroxid/carbonate expected in an alkaline and carbonatic soil (Clemente and Bernal, 2006;Bianchi et al, 2008). These results confirm the findings of an experiment carried out in a similar environment (Fagnano et al, 2011).…”
Section: Soil Potentially Toxic Elements Contentsupporting
confidence: 77%
See 1 more Smart Citation
“…The effect of compost on Cd bioavailability could be related to chelating/complexing reactions by acid functional groups of humic substances that can reduce the precipitation as hydroxid/carbonate expected in an alkaline and carbonatic soil (Clemente and Bernal, 2006;Bianchi et al, 2008). These results confirm the findings of an experiment carried out in a similar environment (Fagnano et al, 2011).…”
Section: Soil Potentially Toxic Elements Contentsupporting
confidence: 77%
“…On the contrary, many organic compounds such as low molecular organic acids (citric and gallic acids) are able to increase Cd, zinc (Zn), copper (Cu) and Ni uptake from soil without environmental risks (do Nascimiento et al, 2006). In some cases, compost fertilisation could be a useful tool to increase metal availability due to the high capacity of metal complexation by humic substances (Clemente and Bernal, 2006;Bianchi et al, 2008), soil fertility due to the soil organic matter buildup (Piccolo et al, 2004;Fagnano et al, 2011), and functional microbial groups (Pepe et al, 2013). Moreover, the effect of exogenous organic matter is pH dependent, allowing an increase in metal availability in alkaline soils (Santibáñez et al, 2008;Fagnano et al, 2011) while this is reduced in low pH soils (Alvarenga et al, 2009;Fornes et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Contradictory results have been obtained from the application of humic acids. Bianchi et al (2008) found increased mobilisation of Cu and Zn, associated with both negligible phytotoxicity in Paspalum vaginatum Sw. and improved metal extraction. Better uptake of Mo in forage in a polluted valley in Austria (meadow rendzina) was observed after application of large quantities (10 g kg -1 w/w, i.e.…”
Section: Humic Acidsmentioning
confidence: 85%
“…There are few limitations to the use of complexing agents. Many synthetic chelators, such as EDTA, Ethylenediamine-N,N 0 -disuccinic acid (EDDS) have low degree of biodegradability (Jiang et al 2003;Wu et al 2005;Bianchi et al 2008;Dermont et al 2008). This problem may be overcome by usage of low phytotoxic and easily biodegradable compounds such as NTA and NLMWOAs (Chen et al 2003;Wenger et al 2003), which are more effective in increasing the metal solubility (Vamerali et al 2010;Rahman and Hasegawa 2011).…”
Section: Chemically Induced Phytoremediationmentioning
confidence: 99%